Histogram affine invariants extraction method based on two-scale auto-convolution - Bo HUANG; Xiao-hui ZHAO; Xin-yan CAO; Ji-yin ZHAO; Gong-tao SHI (Tongxin xuebao)
A two-scale auto-convolution histogram affine invariant was proposed.A two-scale auto-convolution transformation was established based on the new image generated by two-dimensional linear transform of image coordinates.Then the value of the new image density function is transformed into the histogram intervals partition and the proposed histogram affine invariant is obtained.In addition,the possible parameter ranges of the new invari are analyzed and the detailed deduction is given.By using the classic ＆quot;fish＆quot;and ＆quot;coil-100＆quot;test database,the effectiveness of the proposed invariant is verified by comparing to the multi-scale auto-convolution normalized histogram affine invariants from the perspective of time efficiency,anti-image distortion,and anti-viewing angle changes.